Saponins from Saponaria officinalis L. Augment the Efficacy of a Rituximab-Immunotoxin - Gilabert-Oriol, Roger; Thakur, Mayank; Haussmann, Katy; Niesler, Nicole; Bhargava, Cheenu; Görick, Cornelia; Fuchs, Hendrik; Weng, Alexander (Planta Medica, 2016)
Triterpenoidal saponins are synthesized in the roots of Saponaria officinalis L. The same plant is also a source for the toxin Saporin, which is a ribosome-inactivating protein. Triterpenoidal saponins are known to increase the cytotoxicity of Saporin by modulating its intracellular trafficking. Here, we investigated if the combinatorial effects elicited by purified saponins and Saporin can be applied to increase the therapeutic efficacy of the immunotoxin Saporin-Rituximab. First, saponins were purified by high-performance liquid chromatography. Thereafter, their intrinsic cytotoxicity was evaluated on Ramos cells with no observed effect up to 5 µg/mL, however, saponins increased the cytotoxicity of Saporin, while no influence was observed on its N-glycosidase activity. Saporin-Rituximab bound to CD20 in Ramos cells and, in the absence of saponins, had a GI50 (concentration inhibiting cell growth to 50 %) of 7 nM. However, in the presence of a nontoxic concentration of saponins, the GI50 of Saporin-Rituximab was 0.01 nM, a nearly 700-fold increase in efficacy. Moreover, two further immunotoxins, namely Saporin-anti-CD22 and Saporin-anti-CD25, were tested in combination with saponins yielding enhancement factors of 170-fold and 25-fold, respectively. All three receptors are present in Ramos cells and the differences in cytotoxicity enhancement may be explained by the differing expression levels of the cellular receptors. The application of purified saponins from S. officinalis L. is therefore a new strategy to potentially improve the cytotoxicity and therapeutic efficacy of Rituximab-immunotoxins for the treatment of B-cell lymphoma.
Keywords: saponin; immunotoxin; Saporin; Rituximab; anti-CD22; anti-CD25; Saponaria officinalis; Caryophyllaceae